Assessment of Iron Contamination in Groundwater of Catchment Area Water - Aichetou Brahim Boutebib; Abdoulaye Demba N’diaye; Sid’Ahmed Baba Elhoumed; Bocar Kalidou M’Baye; Youssef Aoulad El Hadj Ali; Belkheir Hammouti; Bakari Mohamed Semega (Universitas Pendidikan Indonesia, 2023)
This study investigates the occurrence of iron (Fe) in the catchment area water in Derwiche from Hodh El Chargui in Mauritania. The study area was monitored during January and August. The occurrence of Fe in the groundwater showed significant spatial and temporal fluctuations. The relationship between Fe and some physicochemical parameters was also analyzed statistically using Pearson’s correlation matrix. Firstly, the results suggested that the concentration of Fe was influenced by the dissolution of iron minerals. Secondly, the results show that the pH value was an important factor that influenced the Fe concentrations in the groundwater. The Water Quality Index (WQI) method was used to evaluate the suitability for human consumption. The results show that WQI is strongly influenced by Fe indicating that Fe removal would contribute to excellent well water. The Treatability Index (TI) is used to assess water quality. TI confirms the results obtained by the WQI. However, TI also shows that the pH is a parameter to be optimized for possible potabilization. These results show that there would be a close relationship between the recorded Fe levels and the pH. TI confirms the results obtained by Pearson’s correlation matrix. Therefore, the presence of high Fe concentrations in groundwater in the study area could have a natural origin. The results recommended that different treatment techniques should be employed to purify groundwater before consumption. The primary focus should be cascaded toward Fe contamination.